The Pilgrims Society and public diplomacy, 1895-1945 - Bowman, Stephen (College teacher) (Edinburgh studies in Anglo-American relations., 2018)
Drawing on rich archival research, this book explores how the elite network of the Pilgrims Society - whose members included J.P. Morgan and Andrew Carnegie - attempted to influence the Anglo-American relationship in the days before it became special'.